PENGARUH DISKON DAN EFEKTIVITAS CHATBOT OTOMATIS TERHADAP KEPUASAN PELANGGAN DI APLIKASI SHOPEE (STUDI MAHASISWA UNIVERSITAS ISLAM NEGERI SULTHAN THAHA SAIFUDDIN JAMBI ANGKATAN 2022) - Elidya Yahya, Ananda; Saputra Siregar, Erwin; Ifazah, Laily (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digital promotions and automated customer service are increasingly used by e-commerce platforms to shape customer experience. This study examined the effects of discounts and automated chatbot effectiveness on customer satisfaction in the Shopee application among students of Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, cohort of 2022. A quantitative design was applied. The population consisted of 2,816 active students, and 97 respondents were selected using purposive sampling; the sample size was calculated using the Slovin formula with a 10% error tolerance. Data were collected through an online Likert-scale questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares with SmartPLS. The results showed that discounts had a positive and significant effect on customer satisfaction (path coefficient = 0.461; t = 4.413; p = 0.000). Automated chatbot effectiveness did not have a significant partial effect (path coefficient = -0.212; t = 0.986; p = 0.324). Together, both variables had a significant effect on customer satisfaction (F = 12.866; p = 0.000), with R-square = 0.215. However, the measurement model did not meet the ideal reliability and convergent-discriminant validity criteria; therefore, the structural findings should be interpreted cautiously. The findings indicate that the economic value generated by discounts was more influential than chatbot effectiveness in shaping satisfaction among the respondents.